Gender Power Relations, Emotional Regulation, and Family Resilience in Domestic Violence: A Systematic Review - Melati Puspitajati Adikusuma; Imam Machali; Suyadi; Rohinah; Zahro Aulia; Khoirotin (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
“Domestic violence” (DV) is a multidimensional phenomenon shaped by gender power imbalances, economic pressures, and individuals’ capacity for emotional regulation. This study analyzes the interrelationships among gender power dynamics, emotional regulation, and family resilience as both risk factors and protective factors for DV, and formulates their theoretical and practical implications. Using a systematic literature review approach guided by PRISMA, a total of 71 articles and books (2020–2025) from Google Scholar, Connected Papers, and Scispace were analyzed thematically following Braun and Clarke’s six-step method, with an interrater agreement of 0.93. The results indicate that patriarchal culture, economic pressure, and deficits in emotional regulation consistently increase the risk of physical, verbal, sexual, and economic violence, with emotional regulation serving as a mediator bridging structural factors and aggressive behavior. Conversely, family resilience—through open communication, adaptive coping, and social support—serves as a protective factor, although the effectiveness of women’s economic empowerment is context-dependent. These findings underscore the need for integrated interventions that combine psychoeducation, family economic empowerment, gender norm transformation, and inter-institutional synergy.